Entry modes and franchising as a growth strategy for international expansion: Case of Starbucks - SINGH, ABHIJIT (2012)
This research aims to investigate the various entry mode strategies used by firms to enter new foreign markets and the different set of factors that influence its choice in deciding a specific entry mode. This study also points out that why international firms adopt different entry mode strategies for various overseas markets depending on the business environment. It is seen that in this era of globalization, all the multi national companies are trying to expand in different parts of the globe but with different strategies. I found it very intriguing to identify companies using multiple strategies in the same country in order to increase their influence over the market. Therefore, the aim of this research is to find the entry modes used by companies to enter a market and the reasons behind their decision to follow this strategy and the various reasons, which prompted the company to modify their strategies for international growth. In this case study we will look at the particular case of Starbucks Coffee Company’s operations in the United Kingdom.